Uso de la tecnología y el rendimiento académico en los estudiantes de sexto grado en la Unidad Educativa Adolfo Páez - Mosquera Tapia, Ruth Belén (2022)
The purpose of this research study was to determine the influence of the use of technology on academic performance in sixth grade students of parallel A and B of the "Adolfo Páez" Educational Unit. So that the proposed hypothesis seeks to investigate how the use of technology has a negative impact on the academic performance of students, which has a cognitive behavioral psychological approach, therefore, a population of 60 students was obtained, where the sample is constituted by an accidental non-probabilistic sample with a total of 25 students. This is based on a mixed research approach (qualitative/quantitative), type of correlational research, which will allow us to measure the degree of relationship that exists between the use of technology in academic performance, non-experimental design in a way that will allow us to define the variables without manipulating them. The techniques and instruments that are used to collect information on the use of technology variable, which will be used in a survey such as a questionnaire of closed questions, in order to obtain information on the student's academic process, as well as An interview was used as an open-ended questionnaire, so that information on the follow-up of the educational process of the students could be collected, and for the variable of academic performance, PMA primary mental aptitude psychometric test to be able to determine which are the main skills related to student intelligence and grade record analysis.